x-2/3=x+3/2

Simple and best practice solution for x-2/3=x+3/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2/3=x+3/2 equation:



x-2/3=x+3/2
We move all terms to the left:
x-2/3-(x+3/2)=0
We add all the numbers together, and all the variables
x-(+x+3/2)-2/3=0
We get rid of parentheses
x-x-3/2-2/3=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 98=3x+4(5x-10) | | 4p-4=6p-17 | | 9x+18=6x+39 | | 33-4x=2x-13 | | 5t−6=2t+18 | | 700=4.5(120)+4.5x | | -7x-(4×-3)=58 | | 6(2x+4)=(3x+6) | | 3-c/3=3 | | 33−c​ =−3 | | X^-8x+12=0 | | x+1+3=8x | | -4+34=10x+5x-3-1 | | 4^x+2=48 | | 2x+2/2=2x+2/3 | | x²+4=0 | | 4x+2/3=7/2 | | 0=-2x^2+12x+10 | | 1/2m-1/4=1/12m+1/2,m=-3/5 | | 1/3(a+3)(a-3)=2a-6 | | 5y-2/5=3 | | O.4y+0.8=0.1-0.3y | | 4(2r+2)=12 | | 7(2b+2)=42 | | 19=2z+18 | | 5/12m-1/12=0 | | 4x(14-)=20 | | 1/2m-1/4=1/12m+1/6 | | -5(y-3y)+6=-4(3y-y)+7+17y | | 14=4r+15 | | 7-2n=8n-(-n) | | (3p-1/2)-(p/2-3/2)+(4-p)/2=0 |

Equations solver categories